THERAPEUTIC POTENTIAL OF CAMEL MILK - Dubey, Uma Shukla; Lal, Manohar; Mittal, Anyaa; Kapur, Suman (Emirates Journal of Food and Agriculture, 2016)
Camel milkis recognized for its therapeutic potential against many diseases. It is reported to have microbicidal and immuno stimulatory properties as it contains immunoactive proteins like lysozyme, lactoperoxidase and lactoferrin. Camelid antibodies have a unique structure. Theypossess the heavy chains but are devoid of the usual light chains. This special feature enhances theirpenetration. Camelid proteins have a very high degree of thermal stability and areresistant to acid hydrolysis. Camel milk components act like a ligand to the aryl hydrocarbon receptor.They significantly inhibit the induction of some cancer-activating genes and also induce tumor suppressor genes. Modulation of aryl hydrocarbon receptors is now recognized to have a vital role in cancer therapy. The present review deals with clinical significance of camel milk with special reference to cancer. It also encompasses its unique composition, relevance to otherdiseases and special properties as compared to human milk.